VEGF(165) expressing bone marrow mesenchymal stem cells differentiate into hepatocytes under HGF and EGF induction in vitro - Tan, Yan (Springer Netherlands, 2012)
A short half-life and low levels of growth factors in an injured microenvironment necessitates the sustainable delivery of growth factors and stem cells to augment the regeneration of injured tissues. Our aim was to investigate the ability of VEGF(165) expressing bone marrow mesenchymal stem cells (BMMSCs) to differentiate into hepatocytes when cultured with hepatocyte growth factor (HGF) and epidermal growth factor (EGF) in vitro. We isolated, cultured and identified rabbit BMMSCs, then electroporated the BMMSCs with VEGF(165)-pCMV6-AC-GFP plasmid. G418 was used to select transfected cells and the efficiency was up to 70%. The groups were then divided as follows: Group A was electroporated with pCMV6-AC-GFP plasmid + HGF + EGF and Group B was electroporated with VEGF(165)-pCMV6-AC-GFP plasmid +HGF + EGF. After 14 days, BMMSCs were induced into short spindle and polygonal cells. Alpha-fetoprotein (AFP) was positive and albumin (ALB) was negative in Group A, while both AFP and ALB were positive in group B on day 10. AFP and ALB in both groups were positive on day 20, but the quantity of AFP in group B decreased with prolonged time and was about 43.5% less than group A. The quantity of the ALB gene was increased with prolonged time in both groups. However, there was no significant difference between group A and B on day 10 and 20. Our results demonstrated that VEGF(165)-pCMV6-AC-GFP plasmid modified BMMSCs still had the ability to differentiate into hepatocytes. The VEGF(165) gene promoted BMMSCs to differentiate into hepatocyte-like cells under the induction of HGF and EGF, and reduced the differentiation time. These results have implications for cell therapies.